Proficiency Testing Results for Heparin-Induced Thrombocytopenia in North America - Smock, Kristi J.; Ledford-Kraemer, Marlies R.; Meijer, Piet; Hsu, Peihong; Van Cott, Elizabeth M. (Seminars in Thrombosis and Hemostasis, 2014)
Between 2010 and 2012, North American Specialized Coagulation Laboratory Association (NASCOLA) distributed five proficiency testing challenges to evaluate laboratory testing for heparin-induced thrombocytopenia (HIT). Results (n = 355) were submitted from 43 unique laboratories for 10 samples (3 positive, 2 weak positive, and 5 negative). The vast majority of results were from commercial enzyme-linked immunosorbent assay (ELISA) methods, predominantly polyvalent assays. Laboratories performed well in the classification of clear negative and positive samples. All results (100%) submitted for the five negative samples (n = 173) and 97% of immunological results submitted for the three positive samples (n = 105) were correctly classified (the incorrect responses were two borderline classifications and, from a gel-agglutination method, one negative classification). There was more difficulty in the classification of the two weak positive samples (n = 70). In one survey, 61% of results from the weak positive sample were classified as positive, while 21% were called negative, 16% were called borderline, and 2% were called inconclusive. In a second survey, 16% of results from the weak positive sample were called positive, while 56% were called negative, and 28% were called borderline. Significant interlaboratory variation was observed for ELISA results, with coefficients of variation of about 20 to 30%. We conclude that there is variability in HIT laboratory testing and that identification of weak positive samples can be challenging.
Keywords: heparin-induced thrombocytopenia; proficiency testing; ELISA; NASCOLA; ECAT